Global regularity for the initial–boundary value problem of the 2-D Boussinesq system with variable viscosity and thermal diffusivity - Sun, Yongzhong; Zhang, Zhifei (Journal of Differential Equations, 2013)
We prove the global existence of strong solution to the initial–boundary value problem of the 2-D Boussinesq system and 3-D infinite Prandtl number model with viscosity and thermal conductivity depending on the temperature.